Bad Reading Habit: A Cause of Poor Academic performance and Low Health Standard among Library and Information Sciences Students, University of Jos, Nigeria - Ezeala, Lily Oluebube (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
This paper investigated bad reading habit: A cause of poor academic performance and low health standard among University of Jos, library and information sciences students Plateau State, Nigeria. The study was poised by the moribund state of reading habits among students. The study formulated 5 research questions which includes; what are the causes of bad reading habit? What are the consequences of bad reading habit on the health of Library and Information Science students? among others. Paper adopted a survey research type and cross-sectional research design. The population of the study consisted of 376 undergraduate library and information science students of University of Jos for the academic session 2018/1019. Simple random sampling technique was used in selecting the sample size of 150 which was used for the study. The instrument used for data collection in the study was a structured questionnaire otherwise referred to as close ended questionnaire. Face and content validity was established for the instrument while the reliability index was established using Alpha Cronbach. To be 0,87 which made the instrument reliable for use. Face to face method of data collection was adopted using the instrument (questionnaire) and the analysis was conducted using simple percentage. The study concluded among others that, Bad reading habit amongst students have significant negative impact on their academic achievement and health condition. Amongst the recommendations made by the study includes; Students should be encouraged to borrow books from the library regularly since this can help them to inculcate reading habits.